Analysis of whole genome sequencing and virulence factors of Vibrio vulnificus 1908-10 isolated from sea water at Gadeok island coast - Oh, Hee-kyung; Kim, Nameun; Kim, Do-Hyung; Shin, Hye-Young; Lee, Eun-Woo; Eom, Sung-Hwan; Kim, Young-Mog (Fisheries and aquatic sciences, 2023)
Vibrio vulnificus is an aquatic bacterium causing septicemia and wound infection in humans. To understand this pathogen at the genomic level, it was performed whole genome sequencing of a cefoxitin-resistant strain, V. vulnificus 1908-10 possessing virulence-related genes (vvhA, viuB, and vcgC) isolated from Gadeok island coastal seawater in South Korea. The genome of V. vulnificus 1908-10 consisted of two circular contigs and no plasmid. The total genome size was estimated to be 5,018,425 bp with a guanine-cytosine (GC) content of 46.9%. We found 119 tRNA and 34 rRNA genes respectively in the genome, along with 4,352 predicted protein sequences. Virulence factor (VF) analysis further revealed that V. vulnificus 1908-10 possess various virulence genes in classes of adherence, antiphagocytosis, chemotaxis and motility, iron uptake, quorum sensing, secretion system, and toxin. In the comparison of the presence/absence of virulence genes, V. vulnificus 1908-10 had fur, hlyU, luxS, ompU, pilA, pilF, rtxA, rtxC, and vvhA. Of the 30 V. vulnificus comparative strains, 80% of the C-genotype strains have all of these genes, whereas 40% of the E-genotype strains have all of them. In particular, pilA were identified in 80% of the C-type strains and 40% of the E-type strains, showing more difference than other genes. Therefore, V. vulnificus 1908-10 had similar VF characteristics to those of type C strains. Multifunctional-autoprocessing repeats-in-toxin (MARTX) toxin of V. vulnificus 1908-10 contained 8 A-type repeats (GXXGXXXXXG), 25 B.1-type repeats (TXVGXGXX), 18 B2-type repeats (GGXGXDXXX), and 7 C-type repeats (GGXGXDXXX). The National Center for Biotechnology Information (NCBI) Basic Local Alignment Search Tool (BLAST) showed that the RtxA protein of V. vulnificus 1908-10 had the effector domain in the order of cross-liking domain (ACD)-C58_PaToxP-like domain- α/β hydrolase-C58_PaToxP-like domain.